A new scheme for boosting in situ Fenton-like reaction in plant pathogenic tissues for selective structural degradation of capsid proteins - Jun Ma; Ming Chen; Yujie Wang; Jiaying Li; Jian Tang; Shengjun Wu; Chi He; J. Paul Chen (Journal of Nanobiotechnology)
Abstract Safe prevention and control of plant viruses is a global challenge. Inducing viral capsid protein (CP) degradation via hydroxyl radicals (∙OH) generated by an in situ Fenton-like reaction within plant pathogenic tissues is proposed for combating plant viruses in this study. We designed a new Fenton-like reaction inducer, tCuinter-bCDs, which utilizes an internal doping strategy that reduces copper content by 89.89% compared to conventional doping methods, while still achieving a high coexistence of multivalent copper ions. Our research demonstrated that tCuinter-bCDs possessed functional activity to specifically recognize and proximally degrade CP. tCuinter-bCDs form complexes with CP monomers through supramolecular bonds characterized by significant electrostatic components. Within 10 min, the complex induced complete degradation of tertiary structure pockets composed of α-helices and β-sheets located at residues MET1-GLU23, TYR73-ARG93, and SER147-PRO157. Based on a high-resolution 2.91 Å CP model that was constructed for the first time, this degradation process is likely driven by hydrophobic interactions between tCuinter-bCDs and CP residues MET1, VAL5, THR55, and THR58, along with hydrogen bonds formed with THR4, VAL5, GLY15, PRO57, and ALA59, thereby promoting degradation of adjacent peptide segments. This represents the first study demonstrating in situ Fenton-like reactions to combat pathogens in plant systems. Our findings provide a new, efficient, and environmentally friendly approach for plant virus control. Graphical Abstract